Spatial scale of genetic structuring in coastal cod Gadus morhua and geographic extent of local populations - Jorde, Per Erik; Knutsen, Halvor; Espeland, Sigurd Heiberg; Stenseth, Nils Christian (Marine Ecology Progress Series, 2007)
We estimated the spatial scale of genetically distinguishable populations of coastal Atlantic cod Gadus morhua using microsatellite DNA markers. Significant overall heterogeneity in allele frequencies was found among 5 cod samples (n = 493) along a 79 km segment of the Norwegian Skagerrak coast (FST = 0.0013; p = 0.021). Most (3 out of 4) samples separated by less than 30 km were genetically highly similar (FST < 0), whereas more distantly separated samples were typically genetically different. This genetic differentiation pattern indicates a patchy population structure with local coastal cod populations being limited in geographic extent to approx. 30 km or less. The spatial structure is thus on the scale of local fjords, suggesting a role for local topography in shaping population structure. The population structuring of coastal cod is more fine-scaled than hitherto reported, but is consistent with mark–recapture studies and data on egg distributions, and emphasises the need to focus on local populations in the management of marine fishes.